Hydrophobic Modification of Bentonite: Unravelling the Impacts of Aluminium Cation on Silica-Water Interface (Annual Transactions of the Nordic Rheology Society, 2024)
Silica, a predominant metal oxide and fundamental component of the Earth’s crust, exerts significant influence on diverse geochemical and industrial processes through its interactions with water. This study delves into the surface modification of bentonite clay, as a naturally occurring aluminosilicate source, via treatment with varied concentrations of Al(NO3)3, as a novel surface modification approach, and H2 SO4, as a control technique. The obtained results elucidated important alterations in micro-scale surface characteristics, colloidal stability, and rheological behaviour of the aqueous solutions derived from the modified bentonite samples. Zeta potential analyses showed shifts from a stable colloidal solution in untreated bentonite to heightened instability following aluminium nitrate (and acid) treatment(s). In addition, micro-scale surface analyses employing scanning electron microscope (SEM) with energy dispersive spectroscopy (EDS) and Fourier-transform infrared (FTIR) revealed significant changes, encompassing heightened degree of coagulation, caused by intensified neutralization, and diminished swelling capacities induced by surface modifications. EDS analysis validated cation exchange processes and intensified agglomeration with Al(NO3)3 treatment. Furthermore, the stability and rheological behaviour of resulting aqueous fluids demonstrated reduced stability in Al(NO3 )-treated samples, comparable to acid-treated samples, indicative of hydrophobic surfaces post-treatment. The findings highlighted the effectiveness of the applied treatment technique, emphasizing practical implications for surface-treated bentonite utilization in different environments. However, observed variations influenced by ion type and concentration prompt the imperative for further research to unveil specific mechanisms of treatment approaches on aluminosilicate systems. This endeavour contributes to advancing comprehension and optimization of silicate performance across diverse applications.